2014
DOI: 10.1038/nature13764
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of broadly influenza neutralizing antibodies through redundant mutations

Abstract: The neutralizing antibody response to influenza virus is dominated by antibodies that bind to the globular head of haemagglutinin, which undergoes a continuous antigenic drift, necessitating the re-formulation of influenza vaccines on an annual basis. Recently, several laboratories have described a new class of rare influenza-neutralizing antibodies that target a conserved site in the haemagglutinin stem. Most of these antibodies use the heavy-chain variable region VH1-69 gene, and structural data demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
331
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(351 citation statements)
references
References 39 publications
17
331
3
Order By: Relevance
“…For example, there are many mutations in A:T around residue 280, where the A:Ts are between two simple AID hotspots that mutate at an intermediate frequency, and as in the CDR2, there are no AID cold spots. Mutations in FW3 have been observed previously (62), and recent studies (1,30) have revealed the importance of mutations, and even deletions and insertions, in the FWs in the broadly neutralizing capacity of antibodies to HIV and influenza. In addition, it has been suggested that mutations in the FW are necessary to stabilize the structure of the CDRs (31).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For example, there are many mutations in A:T around residue 280, where the A:Ts are between two simple AID hotspots that mutate at an intermediate frequency, and as in the CDR2, there are no AID cold spots. Mutations in FW3 have been observed previously (62), and recent studies (1,30) have revealed the importance of mutations, and even deletions and insertions, in the FWs in the broadly neutralizing capacity of antibodies to HIV and influenza. In addition, it has been suggested that mutations in the FW are necessary to stabilize the structure of the CDRs (31).…”
Section: Discussionmentioning
confidence: 75%
“…The black vertical lines are mutations in dC on either strand and are presumed to have been initiated by the direct action of AID, whereas the gray vertical lines are mutations in A:T residues and are presumed be a result of error-prone MMR (47). After recent precedents (1,30,48), the CDRs indicated by the horizontal gray bars at the top of the figure are based on the Kabat criteria (49) combined with analysis of the crystal structure of the IGHV3-23*01 V region, rather than the IMGT definition (48). It is obvious that the frequency of these independent and unique somatic mutations in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The V3-glycan PCDN, BF520-derived and DH270 bnAb lineages share some common traits: 1) differently from previously described V3-gylcan bnAbs (23, 25), their evolution did not involve insertion/deletion (indel) events, demonstrating that indels are not a universal requirement for the V3-glycan bnAb class to acquire neutralization breadth; 2) neutralization breadth was acquired with relatively modest levels of somatic hypermutation that can be achieved through vaccination (57, 60, 61), and 3) the UCA of the V3-glycan lineages did not neutralize or bind autologous TF suggesting the hypothesis that V3-glycan bnAb lineages may arise in response to altered forms of the Env protein.…”
Section: Antibody-virus Co-evolutionmentioning
confidence: 94%
“…These bnAbs bind the influenza hemagglutinin glycoprotein (HA; Wilson et al, 1981) and target functionally conserved epitopes on the HA head and stem regions (Lee & Wilson, 2015). In conjunction with these advances in antibody discovery, the developmental pathways that the HA stem-targeted V H 1-69-encoded antibodies take to convert from germline to affinitymatured forms are an active area of investigation (Lingwood et al, 2012;Avnir et al, 2014;Pappas et al, 2014). These studies show that somatic mutations that arise during the affinitymaturation process can affect the conformations of the antibody complementarity-determining region (CDR) loops.…”
Section: Introductionmentioning
confidence: 99%